Sustainable Development of Organic Agriculture in Kazakhstan: Regional Сontex - R. S. Bespayeva; R. A. Karabassov; N. N. Nurmukhametov; R. O. Bugubayeva (Экономика: стратегия и практика)
The purpose of the study is to analyze the state of the rural territory of Kazakhstan and the Akmola region. The study is classified as a desk (marketing) study, the collection and analysis of secondary (preliminary) information was carried out, in particular, data from the FAO statistical yearbook and the website of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan of the Ministry of National Economy of the Republic were used to review and analyze the indicators Kazakhstan. Based on official statistics, an analysis of the state of the rural territory of Kazakhstan and the Akmola region was carried out. The indicators are considered as the gross regional product per capita of the Republic of Kazakhstan, the structure of the gross regional product of the Akmola region, the level of self-sufficiency in agricultural products of the Akmola region, the leading indicators of the development of rural areas of the Akmola region, the harvested area of maagrarianral crops by types of the EAEU countries. The results of the above study - the current relevance of ensuring the sustainable development of rural areas is due, on the one hand, to the growing economic and social lag of the rural regions, and on the other hand, their exceptional importance for the nation in such matters as food security, conservation of soil and environmental resources, the use of agricultural, industrial and labour resources, and their potential.